The development of a protocol for the encapsulation-desiccation and in vitro culture of embryonic axes of Quercus suber L-and Q-ilex L. - Gonzalez-Benito, M E; Herradon, E; Martin, C (SILVAE GENETICA, 1999)
Quercus species have seeds recalcitrant against long-term storage. Cryopreservation of embryonic axes could be a feasible way of preserving their genetic diversity. Several cryopreserva- tion protocols are based on desiccation, among them the so- called encapsulation-dehydration. However, it is previously necessary to establish an adequate in vitro culture develop- ment of desiccated axes. Embryonic axes of Q. suber and Q. ilex were aseptically excised, encapsulated in alginate beads, cultur- ed in a sucrose-rich liquid medium, desiccated for different periods in a flow bench and cultured on basal WPM medium. Moisture content of encapsulated axes dropped from 74% to 71% (fresh weigh basis) to 24.5% to 21% after 6 h desiccation, respectively for the two species. Germination decreased to 20% in both species. Germination and shoot elongation of encapsu- lated embryos (non-desiccated or desiccated for 4 h) was stud- ied for both species after culture on WPM medium supplemented with different concentrations of BAP and IBA. Medium with 0.1 mgl-1 BAP resulted in a high percentage of germina- tion and development of shoots in both species
Keywords: aliginate bead; Dehydration; in vitro culture; oak; Quercus; recalcitrant seed